Enhancement of Solubilityand Dissolution Rate OfRosuvastatin Calcium By Complexation With Î’-Cyclodextrin - V, Akbari B (International Journal of Pharmaceutical & Biological Archive, 2011)
The objective of the study was to increase the solubility, and dissolution rate of Rosuvastatin Calcium (RST), a poorly water-soluble 3-hydroxy3-methyl glut aryl CoA (HMG-CoA) Reductase inhibitor through inclusion complexation with Î²-cyclodextrin (Î²-CD).The phase solubility proï¬le indicated that the solubility of RosuvastatinCa was signiï¬cantly increased in the presence of Î²-CD and Apparent stability constant (KC) wasfound to be 42.003M-1. The inclusion complexes were prepared by three different methods viz. physical, kneading, Co-evaporation and precipitation method. The prepared complexes were characterized using FTIR, Differential scanning Calorimetry and Powder X-ray diffractometry. The inclusion complex prepared with Î²-CD by kneading method exhibited greatest enhancement in solubility and fastest dissolution (98.96% RST release in 30 min) of RST. The inclusion complex containing RST: Î²-CD (1:1) was formulated into tablets using superdisintegrants like sodium starch glycolate, Crosspovidoneand Crosscarmellose. The prepared tablet were evaluated for various post compression parameters like hardness, friability, weight variation, thickness, drug content and in-vitro dissolution. The stability of tablets was studied and no signiï¬cant changes were detected in the dissolution proï¬le of tablets after 1 month.